2003
DOI: 10.1152/ajpcell.00286.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of P2X7 receptor-mediated ERK1/2 phosphorylation in human astrocytoma cells

Abstract: Astrocytes are involved in normal and pathological brain functions, where they become activated and undergo reactive gliosis. Astrocytes have been shown to respond to extracellular nucleotides via the activation of P2 receptors, either G protein-coupled P2Y receptors or P2X receptors that are ligand-gated ion channels. In this study, we have examined the manner in which activation of the P2X(7) nucleotide receptor, an extracellular ATP-gated ion channel expressed in astrocytes, can lead to the phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
83
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 54 publications
7
83
1
Order By: Relevance
“…Erk1/2 phosphorylation is also Ca 2ϩ -independent in rat P2X7R-transfected HEK 293 cells (55) and parotid acinar cells (59). Calcium influx is, on the other hand, needed for Erk1/2 activation in astrocytoma (32) and Jurkat cells (54). Using various deletion mutants of rat P2X7R, Amstrup et al (55) have concluded that the N-terminal domain of P2X7R is essential for triggering Erk1/2 phosphorylation, whereas the C terminus domain controls Ca 2ϩ entry, suggesting that the two events may be dissociable in many cell types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erk1/2 phosphorylation is also Ca 2ϩ -independent in rat P2X7R-transfected HEK 293 cells (55) and parotid acinar cells (59). Calcium influx is, on the other hand, needed for Erk1/2 activation in astrocytoma (32) and Jurkat cells (54). Using various deletion mutants of rat P2X7R, Amstrup et al (55) have concluded that the N-terminal domain of P2X7R is essential for triggering Erk1/2 phosphorylation, whereas the C terminus domain controls Ca 2ϩ entry, suggesting that the two events may be dissociable in many cell types.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither p56 lck nor p59 fyn represent the relevant kinase. The involvement of Src family tyrosine kinase(s) in P2X7R signaling has been described for rat microglia (60) and for Jurkat lymphoma (54) and astrocytoma cells (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the events regulating MAP kinase cascades in activated macrophages are important for the understanding of inflammatory mediator production. In this regard, it is known that ERK1/ ERK2, p38, and JNK1/JNK2 are activated in response to P2X 7 agonists in a variety of cell types [8,[45][46][47][48]. Because P2X 7 action has been linked to inflammatory mediator production [8,49,50], it is likely that nucleotide-mediated MAP kinase activation modulates proinflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…In astrocytes and other glial cells, accumulating evidence indicate that the receptor is coupled to both ERK and p38 mitogen-activated protein kinase (MAPK) phosphorylation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%